2011
DOI: 10.4103/1463-1741.90299
|View full text |Cite
|
Sign up to set email alerts
|

Gender perspectives in psychometrics related to leisure time noise exposure and use of hearing protection

Abstract: The purpose of the present study was to investigate possible gender differences regarding psychometric scales measuring risk perception in noisy situations, attitudes towards loud music, perceived susceptibility to noise, and individual norms and ideals related to activities where loud music is played. In addition the purpose was to analyze whether these variables are associated with protective behavior such as the use of hearing protection. A questionnaire was administered to a Swedish sample including 543 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…This result could suggest that women are more willing to report hearing problems compared with young men. This explanation is consistent with previous results,[ 18 ] in which women report a higher degree of perceived susceptibility to noise but also perceived noise-related risks as more dangerous compared with men. A possible explanation is that it is more acceptable for women to express subjectively experienced hearing symptoms, whereas it is not as acceptable for men.…”
Section: Discussionsupporting
confidence: 93%
“…This result could suggest that women are more willing to report hearing problems compared with young men. This explanation is consistent with previous results,[ 18 ] in which women report a higher degree of perceived susceptibility to noise but also perceived noise-related risks as more dangerous compared with men. A possible explanation is that it is more acceptable for women to express subjectively experienced hearing symptoms, whereas it is not as acceptable for men.…”
Section: Discussionsupporting
confidence: 93%
“…[ 33 ] Information regarding these factors in young adults is important as it can optimize HCPs designed to induce more health-orientated behavior. In the literature, some of these factors are questioned in several populations in relation to confounding variables such as gender, cultural differences, and socioeconomic status,[ 30 44 45 ] or are used to evaluate the effectiveness of a preventive campaign. [ 36 ] However, to our knowledge, this is the first study that evaluates young adults’ hearing status in relation to all suggested variables.…”
Section: Discussionmentioning
confidence: 99%
“…The first 11 statements were a modified version of Youth Attitude to Noise Scale-Revised R (YANS-R). [18] Cronbach's alpha for the YANS-R was α = 0.83, indicating an acceptable reliability of the measurement. Items number 3, 4, 6, 9 and 11 were however reversed scored due to the wording of the items.…”
Section: Measurementsmentioning
confidence: 99%
“…[13,15,16] Empirical research suggests that the individual decision about using hearing protection in noisy situations may be governed by variables such as social norms, attitudes and risk perception. [17,18] In addition, previous studies have found that self-reported permanent tinnitus and sound sensitivity are associated with attitudes toward noise and the decision to wear hearing protection. [19] Although, there is a growing body of research aiming at the risk-taking behavior in noisy settings, there is also a growing need to identify new potentially important variables to be included in work on hearing preventive behavior.…”
Section: Introductionmentioning
confidence: 98%